2020
DOI: 10.2217/nnm-2020-0009
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of Alumina Nanoparticles in The Immune System of Mice

Abstract: Aim: Alumina nanoparticles (AlNPs) exert toxic effects in several organs. This study aimed to investigate the toxicity of AlNPs to the immune system. Materials & methods: AlNPs distribution was assessed using CRi in vivo fluorescence imaging. Inductively coupled plasma atomic emission spectrometry was used to detect the content of aluminum in the spleen. Cytokines expression was detected in the immune organs and blood of mice. Results & conclusion: AlNPs can accumulate in mice spleen. Superoxide dismut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 58 publications
0
19
0
1
Order By: Relevance
“…Additionally, previous studies have also shown that Al 2 O 3 NPs can cause pro‐inflammatory reactions, which may be a risk of cardiovascular disease (Oesterling et al, 2008). Recently, it has been documented that Al 2 O 3 NPs can accumulate in mice spleen, and Al 2 O 3 NPs exposure caused cytokine level changes in the spleen, thymus, and serum, besides causing damage to immune organs and dysfunction of immune cells, leading to abnormal immune‐related cytokine expression (Li et al, 2020). Likewise, using male Wistar rat model, it was found that exposure to Al 2 O 3 NPs and/or HClg aerosols for 4 h (unique exposures) or 4 h a day for 4 days (iterative exposures), primarily manifests the toxicological effects of the mixture, whereas Al 2 O 3 NPs' presence in the aerosols also seems to play essential role in driving toxicity (Bourgois et al, 2020).…”
Section: Nano‐metal Oxidesmentioning
confidence: 99%
“…Additionally, previous studies have also shown that Al 2 O 3 NPs can cause pro‐inflammatory reactions, which may be a risk of cardiovascular disease (Oesterling et al, 2008). Recently, it has been documented that Al 2 O 3 NPs can accumulate in mice spleen, and Al 2 O 3 NPs exposure caused cytokine level changes in the spleen, thymus, and serum, besides causing damage to immune organs and dysfunction of immune cells, leading to abnormal immune‐related cytokine expression (Li et al, 2020). Likewise, using male Wistar rat model, it was found that exposure to Al 2 O 3 NPs and/or HClg aerosols for 4 h (unique exposures) or 4 h a day for 4 days (iterative exposures), primarily manifests the toxicological effects of the mixture, whereas Al 2 O 3 NPs' presence in the aerosols also seems to play essential role in driving toxicity (Bourgois et al, 2020).…”
Section: Nano‐metal Oxidesmentioning
confidence: 99%
“…The spleen and thymus IFN-γ content in the AlNP-exposed mice was significantly higher. Serum IL-4 levels were also decreased, and this decline could affect the autoimmune response mediated by Th1 cells [37].…”
Section: Al and The Immune Systemmentioning
confidence: 99%
“…Alumina (aluminum oxide) nanoparticles (AlNPs) account for about 20% of the global nanoparticle market (Sengul and Asmatulu 2020). They have multiple uses in cosmetics, medicines, electronics, aerospace, chemical engineering, food contact materials, catalysts, ceramics and rubber (Li et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, because the cell surface is negatively charged and AlNPs are positively charged, these particles are drawn to the interior of cells through electrostatic interactions (Liu et al 2020a). This in turn produces many toxic effects including hematological changes (De et al 2020), genotoxicity (Zhang et al 2017), testicular toxicity (De et al 2020), carcinogenicity (Dey et al 2008) immunotoxicity (Li et al 2020), hepatotoxicity, nephrotoxicity (Morsy et al 2016) and pulmonary toxicity (Yun et al 2020).…”
Section: Introductionmentioning
confidence: 99%